Four Battlegrounds power in the age of artificial intelligence - Scharre, Paul. (Norton and Company, 2023)
A new industrial revolution has begun. Like mechanization or electricity before it, artificial intelligence will touch every aspect of our lives―and cause profound disruptions in the balance of global power, especially among the AI superpowers: China, the United States, and Europe. Autonomous weapons expert Paul Scharre takes readers inside the fierce competition to develop and implement this game-changing technology and dominate the future.
Includes index
Keywords: Artificial intelligence